Convergent evolution and possible constraint in the posterodorsal retraction of the external nares in pelagic crocodylomorphs. Issue 2 (11th June 2020) - Young, Mark T; Sachs, Sven; Abel, Pascal; Foffa, Davide; Herrera, Yanina; Kitson, James J N
Abstract: Amongst Mesozoic marine reptiles, metriorhynchid crocodylomorphs were unique in evolving into pelagically adapted forms with little-to-no posterodorsal retraction of the external nares. Narial retraction is a common adaptation seen in sustained swimmers, notably occurring during cetacean evolution. Mesosaurids and the basalmost known members of ichthyosauriforms, thalattosaurians, saurosphargids, sauropterygians, pleurosaurids and mosasauroids had the external nares divided by an ossified bar, bound by multiple cranial bones and were positioned back from the tip of the rostrum. However, metriorhynchids evolved from taxa with a single external naris bound solely by the premaxilla, and positioned near the tip of an elongate rostrum. We posit that metriorhynchids were uniquely disadvantaged in evolving into sustained swimmers. Herein we describe three Late Jurassic metriorhynchid cranial rostra that display differing degrees of narial retraction. In our new phylogenetic analyses, the backwards migration of the narial fossa posterior margin occurred independently at least four times in Metriorhynchidae, whereas the backwards migration of the anterior margin only occurred twice. Although Rhacheosaurini share the backwards migration of the anterior and posterior narial margins, posterodorsal retraction occurred differently along three lineages. This culminated in the Early Cretaceous, where a rhacheosaurin evolved nares bound by the premaxilla and maxilla, and significantly posterodorsally retracted.